Association between ADH1C and ALDH2 polymorphisms and alcoholism in a Turkish sample. (April 2015) - Ayhan, Yavuz; Gürel, Şeref Can; Karaca, Özgür; Zoto, Teuta; Hayran, Mutlu; Babaoğlu, Melih; Yaşar, Ümit; Bozkurt, Atilla; Dilbaz, Nesrin; Uluğ, Berna Diclenur; Demir, Başaran
Abstract: Background: Polymorphisms in the genes encoding alcohol metabolizing enzymes are associated with alcohol dependence. Aim: To evaluate the association between the alcohol dehydrogenase 1C (ADH1C) Ile350Val and aldehyde dehydrogenase 2 (ALDH2) Glu504Lys polymorphisms and alcohol dependence in a Turkish sample. Methods: 235 individuals (115 alcohol-dependent patients and 120 controls) were genotyped for ADH1C and ALDH2 with PCR–RFLP (polymerase chain reaction–restriction fragment length polymorphism). Association between the polymorphisms and family history, daily and maximum amount of alcohol consumed was investigated. The associations between alcohol dependence, severity of consumption and family history and the polymorphisms were analyzed by chi-square or Fisher's exact test where necessary. Relationship between genotypes and dependence related features was evaluated using analysis of variance (ANOVA). Results: The -350Val allele for ADH1C ( ADH1C*2 ) was increased in alcohol-dependent patients ( P = 0.05). In individuals with a positive family history, the genotype distribution differed significantly ( P = 0.031) and more patients carried the Val allele compared with controls ( P = 0.025). Genotyping of 162 participants did not reveal the -504Lys allele in ALDH2. Conclusions: These findings suggest that ADH1C*2 is associated with alcohol dependence in the Turkish population displaying a dominant inheritance model. ADH1C*2 allele may contribute to the variance in heritability of alcohol dependence. The ALDH2 -504Lys/Lys or Glu/Lys genotypes were not present in alcohol-dependent patients, similar to that seen in European populations and in contrast to the findings in the Asian populations.